ANALISIS ANGGARAN KAS SEBAGAI ALAT PERENCANAAN DAN PENGENDALIAN MENINGKATKAN LIKUIDITAS PADA PERUSAHAAN DAERAH PEMBANGUNAN KOTA MEDAN - Noviyanti Siregar; Ova Novi Irama (Program Studi Akuntansi Fakultas Ekonomi UMN AL Washliyah, 2023)
Development of Current ratio in PD. Medan City Development in 2016-2017 from 118.8% to 66.6% In 2017-2018 it decreased from 66.6% to 31.2%, in 2018-2019 it increased from 31.2% to 64.4% and in 2019-2020 experienced a decrease from 64.4% to 47.4%. The increase and decrease in the current ratio above is not good, so it can be concluded that the company is in an illiquid state. The quick ratio decreased in 2016-2017 from 116% to 64.2%, in 2017-2018 it decreased from 64.2% to 30.1%, in 2018-2019 it increased from 30.1% to 63.6 %, in 2019-2020 it decreased from 63.6% to 12.9%. In 2016-2017 the cash ratio decreased from 15.7% to 4.29%, in 2017-2018 it decreased from 4.29% to 1.14%, in 2018-2019 it increased from 1.14% to 1 .19% and in 2019-2020 the cash ratio increased from 1.19% to 1.51%. Based on the research results, the results of the cash budget analysis show that cash does not meet needs because a good Current ratio is at the limit of 200% and cash budget analysis cannot increase liquidity in the Medan City Regional Development Company in the 2016-2020 period because it is not at the standard ratio namely 99.56% for Quick Ratio, 100% for Cash Ratio, and 122% for Current ratio .